2015
DOI: 10.1007/s00134-015-4114-5
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol therapy in intensive and intermediate care units: prospective observation of 2808 critically ill patients

Abstract: Aerosol therapy concerns every fourth critically ill patient and one-fifth of ventilated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 40 publications
1
78
3
2
Order By: Relevance
“…Aerosolized drugs are currently not limited to bronchodilators, but also include glucocorticoids, mucolytics, and antibiotics. In view of the value of many of these drugs, it is necessary to prolong nebulization time in order to minimize the amount of residual drug solution [4]. The factor that ultimately determines the clinical effectiveness of aerosol inhalation is the aerosol deposition rate, which is affected by the diameter of the aerosol particles and the delivery efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerosolized drugs are currently not limited to bronchodilators, but also include glucocorticoids, mucolytics, and antibiotics. In view of the value of many of these drugs, it is necessary to prolong nebulization time in order to minimize the amount of residual drug solution [4]. The factor that ultimately determines the clinical effectiveness of aerosol inhalation is the aerosol deposition rate, which is affected by the diameter of the aerosol particles and the delivery efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients receiving noninvasive ventilation for respiratory failure also require aerosol inhalation of drugs such as bronchodilators, glucocorticoids, mucolytics, and antibiotics [4]. Research has found aerosol inhalation therapy in conjunction with noninvasive ventilation to be a more effective method of drug delivery than conventional nebulization (in between noninvasive positive pressure ventilation sessions) [5].…”
Section: Introductionmentioning
confidence: 99%
“…A follow-up study by the same group utilized a cross-sectional point prevalence study over 14 days in 81 ICUs in 22 countries including 2,808 patients (283). A total of 678 (24%) patients received at least one inhaled medication during the study period, about half of whom were patients who were intubated.…”
Section: Nosocomial Pneumoniamentioning
confidence: 99%
“…Many drugs are administered as aerosol [2] using nebulizers for treatment of intubated mechanically ventilated patients [3].…”
Section: Introductionmentioning
confidence: 99%